Enhancing the Management and Recycling Capacity of Styrofoam Waste Through a Green Economy Approach - Setyono, Gatot; Rodhiyah, Rodhiyah; Ulum, Miftahul; Haryadi Ogsa, Muhammad Al Khawarizmi; Aditya, Bagas (Jurnal Pustaka Mitra (Pusat Akses Kajian Mengabdi Terhadap Masyarakat), 2025)
Styrofoam waste poses a serious environmental challenge due to its non-biodegradable nature and the lack of sustainable disposal solutions. Conventional methods such as landfilling and incineration often lead to secondary problems, including soil contamination and harmful emissions. This community partnership program was conducted at UD Tiga Putra, a micro-enterprise in Gresik, Indonesia, which previously relied on a 150 kg/day Styrofoam melting machine prone to frequent breakdowns and inconsistent product quality. To address these issues, an appropriate-technology Styrofoam melting machine with a capacity of 300 kg/day was introduced, effectively doubling production capacity (from 150 to 300 kg/day) and improving product uniformity. In addition, structured occupational health and safety (OHS) training was provided to 12 employees, covering fire extinguisher (APAR) usage, personal protective equipment, and workplace safety practices. Financial mentoring was also delivered, emphasizing systematic bookkeeping, separation of personal and business finances, and preparation of transparent reports. Evaluation using pre- and post-training assessments and direct observation showed significant improvements: OHS awareness scores increased by 20%, financial documentation accuracy improved, and operational disruptions decreased. Overall, the integration of technological innovation, safety training, and financial management mentoring not only strengthened the resilience and sustainability of UD Tiga Putra but also offers a replicable model for empowering other micro-enterprises in line with circular economy principles.